Quality Control Management Practices in a Semiconductor Company in Laguna, Philippines and its Impact on Customer Satisfaction - Rivera, Racquel G; Briones, Jesus; Baldovino, Flormando P (Research Synergy Foundation, 2023)
Quality control management practices (QCMP) are a driving force in augmenting organizational quality performance. This study determined the QCMP of a semiconductor company in Laguna, Philippines and assessed its perceived impact on customer satisfaction. A researcher-made survey instrument was validated and pilot-tested, establishing a Cronbach Alpha of 0.892. The surveyed respondents are 150 employees of the subject-semiconductor company who consented to participate in the study. The collected data were analyzed utilizing frequency, percentage, weighted mean, and ANOVA. The study found that employees were aware of the implementation of company-wide QCMP, and they likewise perceived that the quality system was appropriately set in place. The study proved that the company's dedication to continuous improvement and employee engagement leading to customer satisfaction is evident. Moreover, the study also proved that profile indicators employed in the study are not varying factors for the company's QCMP implementation. To continue reaping the highest implementation, it is recommended that the company sustain the commitment to maintain its QCMP through continuous training, employee feedback, exploring opportunities, better customer relations, and enhancing cross-functional processes.